2013
DOI: 10.1186/1471-2334-13-409
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of pneumococcal serotype 1 carriage during an outbreak of serotype 1 invasive pneumococcal disease in central Australia 2010–2012

Abstract: BackgroundAn outbreak of serotype 1 invasive pneumococcal disease (IPD) occurred in Central Australia from October 2010 to the latter part of 2012. Surveillance of serotype 1 carriage was conducted to determine epidemiological features of asymptomatic carriage that could potentially be driving the outbreak.Methods130 patients and accompanying persons presenting at Alice Springs Hospital Emergency Department consented to nasopharyngeal swab (NPS) collection. NPS were processed by standard methods, including cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Serotype 1 is ranked among the most common invasive serotypes worldwide and is often associated with outbreaks and epidemics [3][4][5][6][7][8][9][10][11][12][13]. Unlike other pneumococci responsible for invasive pneumococcal disease (IPD), serotype 1 pneumococci are rarely found in the nasopharynx of healthy individuals in the general population [14][15][16][17][18]; however, carriage in healthy contacts has been observed during times of serotype 1 outbreaks [9], including in one carriage surveillance study undertaken during a serotype 1 outbreak which demonstrated carriage of the outbreak strain in healthy children [19].…”
Section: Introductionmentioning
confidence: 99%
“…Serotype 1 is ranked among the most common invasive serotypes worldwide and is often associated with outbreaks and epidemics [3][4][5][6][7][8][9][10][11][12][13]. Unlike other pneumococci responsible for invasive pneumococcal disease (IPD), serotype 1 pneumococci are rarely found in the nasopharynx of healthy individuals in the general population [14][15][16][17][18]; however, carriage in healthy contacts has been observed during times of serotype 1 outbreaks [9], including in one carriage surveillance study undertaken during a serotype 1 outbreak which demonstrated carriage of the outbreak strain in healthy children [19].…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting result was the detection of serotype 1 in carriers. This is a rare event even in areas where such serotype is the main cause of IPD, usually reported only during outbreaks of this serotype [26]. Some studies have suggested that the lack of serotype 1 detection in carriers could be due to the lack of techniques able to detect multiple colonization [27,28].…”
Section: Discussionmentioning
confidence: 96%
“…70,71 The other factor contributing to relatively modest impact of 13vPCV in Aboriginal and Torres Strait Islander children is an outbreak of serotype 1 IPD among children living in central and northern parts of the country in 2010-2012. 72,73 The serotype 1 outbreak primarily affected older Aboriginal children, resulting Other sero 7vPCV 13v-non-7v 23v-non-13v…”
Section: Discussionmentioning
confidence: 99%